Fumarprotocetraric acid and geraniin were identified as novel inhibitors of human respiratory syncytial virus infection in vitro - Chao Wang; Chao Wang; Yi-Man Huang; Yi-Man Huang; Jun Zhao; Jun Zhao; Yi-Ming Bai; Yi-Ming Bai; Cai-Qin Yan; Cai-Qin Yan; Guan-Hua Du; Guan-Hua Du; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionRespiratory syncytial virus (RSV) remains a major international public health concern. However, disease treatment is limited to preventive care with monoclonal antibodies and supportive care. In this study, natural products were screened to identify novel anti-RSV inhibitors.MethodsThe antiviral effect of 320 compounds on RSV in HEp-2 cells was tested using a Cytopathic effect (CPE) inhibition assay. The antiviral effect of fumarprotocetraric acid (FUM) and geraniin (GE) were confirmed by Real-time reverse transcription quantitative PCR (Real-time RT-PCR), plaque reduction test, immunofluorescence assay, and Western blot analysis. Real-time PCR was used to detect inflammatory factor expression. ATP assay and JC-1 stain were used to evaluate mitochondrial protection function. The experiment of administration time was used to determine the stages in the RSV life cycle inhibited by FUM and GE. Human metapneumovirus (HMPV) and human rhinovirus (HRV) were used to evaluate the antiviral activities of other respiratory viruses of FUM and GE. Finally, Air-liquid interface human airway epithelium (ALI-HAE) cells were used to evaluate the antiviral effect and mechanism of FUM and GE to RSV.ResultsThe results showed that FUM and GE can inhibit the replication of RSV in multiple-cell models. Both compounds could dose-dependent inhibit the viral load, RSV nucleic acids level, and RSV-F protein level. Besides, FUM and GE showed good anti-inflammatory activity, mitochondrial protection, and antiviral activity to HMPV and HRV. Meanwhile, our result indicated that FUM and GE can inhibit RSV replication in ALI-HAE cells.ConclusionsFUM and GE were identified as new inhibitors of RSV infection. At the same time, FUM and GE have anti-inflammatory activity, mitochondrial protection function, and broad-spectrum antiviral activity. These results provide evidence that FUM and GE are potential candidates for the development of novel anti-RSV drugs.